Lysapsus limellus. Reproductive Traits - Marangoni, Federico (2000)
Lysapsus limellus is restricted to areas along the Paraguay and Parana Rivers, from Rondonia  and Mato Grosso (Brazil) to central Argentina. Within Argentina, L. limellus occurs in the provinces of Chaco, Formosa, Corrientes, and Santa Fe, and north of Buenos Aires (Cei 1980. Amphibians of Argentina. Monit. Zool. Ital. (NS) Monog. 2: 609 pp.). Lysapsus limellus is very aquatic, occurring in semi-permanent and permanent ponds (Hamann and Kehr 1997. Herpetol. Rev. 28: 85; Kehr and Basso 1990. Copeia 1990: 573-575.). Herein we report the firs reproductive traits of the specie.